Assessing effects of deficit irrigation techniques on water productivity of tomato for subsurface drip irrigation system - Hashem, Mahmoud S; El-Abedin, Tarek Zin; Al-Ghobari, Hussein M (International Journal of Agricultural and Biological Engineering, 2018)
Water resources are subjected to ever-increasing supply constraints due to extensive agricultural water demand for irrigated lands. Therefore, water-saving irrigation strategies need to be explored. The present study was conducted to explore the possibilities of using regulated deficit irrigation (RDI) and partial root zone drying irrigation (PRD) methods as water-saving irrigation techniques for subsurface irrigation. The objective of this study are to assess the effects of RDI and PRD irrigation on the water productivity of vegetable crops (tomato) under SSD systems in arid climatic conditions, and to compare the responses of tomato crops to PRD, RDI, and FI under an SSD system in terms of productivity, crop quality, and the amount of water saved. The field experiment was conducted during the fall 2014-2015 and 2015-2016 seasons in an experimental field located on an educational farm owned by the Faculty of Food and Agriculture Sciences Department, King Saud University, Riyadh, Kingdom of Saudi Arabia. An area of 102.7 m2 (13 m × 7.9 m) was allocated for the experiment to manage three treatments: RDI, PRD, and full irrigation (FI). The RDI and PRD treatments received 70% of the irrigation water volume of FI. Each was replicated three times. The most important results indicated that the soil water content (SWC) for the RDI and PRD treatments was lower than that of the FI treatments. FI had the highest stomatal conductance values (gs), while PRD had the lowest stomatal conductance values. The photosynthetic rate (An) was lower under RDI and PRD compared to FI. However, there was no significant change in An between treatments for most readings taken during both time periods, which means that the water saving treatments (PRD and RDI) did not affect the net photosynthesis rate, thereby enhancing irrigation water use efficiency (IWUE) under DI treatments. The water-saving irrigation techniques decreased transpiration rate (T) compared to the FI treatment. The values of the abscisic acid (ABA) contents were higher under PRD and RDI than FI. The marketable yield under the FI treatment yielded the highest values. The fruit quality parameter results showed that the RDI and PRD treatments increased the total soluble solids, vitamin C, and titratable acidity of tomato compared to the FI treatment. Most of the minimum IWUE values were associated with FI. These results indicate the effects of deficit levels on IWUE.Keywords: full irrigation (FI), regulated deficit irrigation (RDI), partial root zone drying (PRD), irrigation water use efficiency (IWUE)DOI: 10.25165/j.ijabe.20181104.3846Citation: Hashem M S, El-Abedin T Z, Al-Ghobari H M. Assessing effects of deficit irrigation techniques on water productivity of tomato for subsurface drip irrigation system. Int J Agric & Biol Eng, 2018; 11(4): 156-167.